AI-assisted anatomical structure recognition and segmentation via mamba-transformer architecture in abdominal ultrasound images - Chang, Shih-Fang; Wu, Po-Yi; Tsai, Ming-Chang; Tseng, Vincent S.; Wang, Chi-Chih (Frontiers in Artificial Intelligence, 2025)
BackgroundAbdominal ultrasonography is a primary diagnostic tool for evaluating medical conditions within the abdominal cavity. Accurate determination of the relative locations of intra-abdominal organs and lesions based on anatomical features in ultrasound images is essential in diagnostic sonography. Recognizing and extracting anatomical landmarks facilitates lesion evaluation and enhances diagnostic interpretation. Recent artificial intelligence (AI) segmentation methods employing deep neural networks (DNNs) and transformers encounter computational efficiency challenges to balance the preservation of feature dependencies information with model efficiency, limiting their clinical applicability.MethodsThe anatomical structure recognition framework, MaskHybrid, was developed using a private dataset comprising 34,711 abdominal ultrasound images of 2,063 patients from CSMUH. The dataset included abdominal organs and vascular structures (hepatic vein, inferior vena cava, portal vein, gallbladder, kidney, pancreas, spleen) and liver lesions (hepatic cyst, tumor). MaskHybrid adopted a mamba-transformer hybrid architecture consisting of an evolved backbone network, encoder, and corresponding decoder to capture long-range spatial dependencies and contextual information effectively, demonstrating improved image segmentation capabilities in visual tasks while mitigating the computational burden associated with the transformer-based attention mechanism.ResultsExperiments on the retrospective dataset achieved a mean average precision (mAP) score of 74.13% for anatomical landmarks segmentation in abdominal ultrasound images. Our proposed framework outperformed baselines across most organ and lesion types and effectively segmented challenging anatomical structures. Moreover, MaskHybrid exhibited a significantly shorter inference time (0.120 ± 0.013 s), achieving 2.5 times faster than large-sized AI models of similar size. Combining Mamba and transformer architectures, this hybrid design was well-suited for the timely analysis of complex anatomical structures segmentation in abdominal ultrasonography, where accuracy and efficiency are critical in clinical practice.ConclusionThe proposed mamba-transformer hybrid recognition framework simultaneously detects and segments multiple abdominal organs and lesions in ultrasound images, achieving superior segmentation accuracy, visualization effect, and inference efficiency, thereby facilitating improved medical image interpretation and near real-time diagnostic sonography that meets clinical needs.